Natural Killer Cell (NK-92MI)-Based Therapy for Pulmonary Metastasis of Anaplastic Thyroid Cancer in a Nude Mouse Model - Zhu, Liya; Li, Xiu Juan; Kalimuthu, Senthilkumar; Gangadaran, Prakash; Lee, Ho Won; Oh, Ji Min; Baek, Se Hwan; Jeong, Shin Young; Lee, Sang-Woo; Lee, Jaetae; Ahn, Byeong-Cheol (Frontiers in Immunology, 2017)
Objective: Natural killer (NK) cells represent the third largest population of lymphocytes, and they are important in immune surveillance against tumors. The lungs are a common metastatic site for anaplastic thyroid cancer (ATC), and metastasis is one of the most frequent causes of mortality related to this type of cancer. In the current study, we evaluated the effects of NK cell-based immunotherapy for pulmonary metastasis of ATC and the effector molecules of NK cells. Methods: Human NK cells (NK-92MI) were retrovirally transduced to express the effluc gene. Human anaplastic thyroid cancer cells (CAL-62) were transduced with the effluc and Rluc genes. The cytotoxicity of NK cells against CAL-62 cells was assessed using the CytoTox 96® Non-Radioactive Cytotoxicity Assay system. Pulmonary metastases of ATC were developed by i.v. injection of CAL-62, and metastasis growth was monitored using bioluminescence imaging (BLI). To treat the metastases, 5 million NK cells were injected twice into the caudal vein. To assess the targetability of NK cells to ATC tumors, NK cells expressing the effluc gene (NK/F) were administered through the tail vein of nude mice with a pulmonary metastasis or tumor xenograft. BLI was subsequently performed at 1 h, 3 h, 24 h, and 48 h. Results: NK/F and CAL-62 cells expressing the effluc or Rluc gene (CAL-62/F, CAL-62/R) were successfully established. Expression of the effluc and Rluc genes in the NK/F, CAL-62/F, and CAL-62/R cells was verified by RT-PCR, western blotting, and luciferase assay. After co-culture of the NK and CAL-62/F cells for 24 h, the BLI signal intensity of CLA-62/F cells proportionally decreased with the number of the cocultured NK cells. An ATC pulmonary metastasis mouse model was successfully generated, and NK cells significantly inhibited the growth of the metastasis (p < 0.01). The NK/F cells exhibited targetability to the pulmonary metastasis and tumor xenograft in the mouse model. Conclusion: The results of present study suggest that NK cells are able to target ATC tumors and that NK cell-based immunotherapy may serve as an effective therapeutic approach for pulmonary metastases of ATC.